The CzcCBA Efflux System Requires the CadA P-Type ATPase for Timely Expression Upon Zinc Excess in Pseudomonas aeruginosa - Ducret, Verena; Gonzalez, Manuel R.; Leoni, Sara; Valentini, Martina; Perron, Karl (Frontiers in Microbiology, 2020)
Zinc (Zn) is a trace element essential for life but can be toxic if present in excess. While cells have import systems to guarantee a vital Zn intracellular concentration, they also rely on export systems to avoid lethal Zn overload. In particular, the opportunistic pathogen Pseudomonas aeruginosa possesses four Zn export systems: CadA, CzcCBA, CzcD, and YiiP. In this work, we compare the importance for bacterial survival of each export system at high Zn concentrations. We show that the P-type ATPase CadA, and the efflux pump CzcCBA are the main efflux systems affecting the bacterium tolerance to Zn. In addition, cadA and czcCBA genes expression kinetics revealed a hierarchical organization and interdependence. In the presence of high Zn concentrations, cadA expression is very rapidly induced (<1 min), while czcCBA expression occurs subsequently (>15 min). Our present data show that the fast responsiveness of cadA to Zn excess is due to its transcriptional activator, CadR, which is constitutively present on its promoter and promptly activating cadA gene expression upon Zn binding. Moreover, we showed that CadA is essential for a timely induction of the CzcCBA efflux system. Finally, we observed an induction of cadA and czcCBA efflux systems upon phagocytosis of P. aeruginosa by macrophages, in which a toxic metal boost is discharged into the phagolysosome to intoxicate microbes. Importantly, we demonstrated that the regulatory link between induction of the CzcCBA system and the repression of the OprD porin responsible for carbapenem antibiotic resistance, is maintained in the macrophage environment.